Impact of Control on Students Evasion of School Fees in Universities - Udom, Idongesit David; Obano, Julian Ezeinmwenghian (Management Research and Behavior Journal, 2024)
The study was undertaken to investigate the impact of control on student evasion of school fees in Nigerian Universities. The purpose was to examine the trending events in the collection of school fees in Nigerian Universities, the position of the Governing Councils of the universities in Nigeria on non-payment of school charges by students in the universities and the major factor that aid evasion of school fees in the universities. The study was necessary because of the impact that control will have on the evasion of school fees in Nigerian universities especially with the current hike in the charges emanating from the withdrawal of education subsidies in higher education in Nigeria.  It was a comprehensive study on Nigerian universities. Information for the study was obtain through the internet and brain-storming. In the brain-storming the researcher interacted with 500 respondents at University of Benin, Benin City, Nigeria, Ambrose Alli University, Ekpoma, Taraba State University, Jalingo. It was an exploratory research that would provide information for future researchers in Student Accounts Management in Universities in Nigeria.  It was found that all Public and Private Universities are making exorbitant charges of school fees in Nigeria. There is huge debt profile arising from non-payment (evasion) of school charges by students in Nigerian Universities. The major factor that aid evasion of school fees in Nigerian Universities is the management flexibility in the enforcement of deadlines for payment of school fees by the students. It found that at these universities the major cause of students evasion of school fees is management flexibility on deadlines for payment of fees. Also, the trending events in Nigeria is the recent withdrawal of educational subsidies on higher education of which the parents and guardian are finding it very difficult to cope with astronomical increases in school fees due to low level of income.  It was concluded that education is no more public goods hence, proposals for enormous increase in Public Universities in Nigeria have assumed alarming and frightening dimension in the country. Therefore, it was recommended that appropriate control measures of the management should be affected for prompt collection of school fees. Contract should be given to Software Companies to assist in the collection of school fees to check fraud in the process. Regular accounting and audit report are necessary to ascertain the state of fees collection to reduce the level of evasion of school fees by students in Nigerian universities.